Sinonasal teratocarcinosarcoma in an adolescent male: A case report of an unusual neoplasm - Aashna Soman; P. H. Prasad; P. V. Ajayan (Indian Journal of Pathology and Microbiology)
Sinonasal teratocarcinosarcoma (SNTCS) is an extremely rare and aggressive malignant tumor arising in the sinonasal tract, having a combined clinicopathological feature of teratoma and carcinosarcoma. It shows a male predominance and affects adults with an age range of 18–79 years and a mean age of 60 years. Here, we report a case of SNTCS in a 14-year-old male patient who presented with swelling over the upper right alveolus and pain in the right jaw for 2 months. The tumor was completely removed by right total maxillectomy with orbital mess reconstruction, and postoperative radiotherapy with chemotherapy was given. The follow-up of the patient for 2 years has shown evidence of recurrence and is now on palliative care.